Lateglacial Shifts in Seasonality Reconcile Conflicting North Atlantic Temperature Signals. Issue 1 (19th January 2023) - Bromley, Gordon; Putnam, Aaron; Hall, Brenda; Rademaker, Kurt; Thomas, Holly; Balter‐Kennedy, Allie; Barker, Stephen; Rice, Donald
Abstract: The accelerating flux of glacial meltwater to the oceans due to global warming is a potential trigger for future climate disturbance. Past disruption of Atlantic Ocean circulation, driven by melting of land‐based ice, is linked in models to reduced ocean‐atmosphere heat transfer and abrupt cooling during stadial events. The most recent stadial, the Younger Dryas (YD), is traditionally viewed as a severe cooling centered on the North Atlantic but with hemispheric influence. However, indications of summer warmth question whether YD cooling was truly year‐round or restricted to winter. Here, we present a beryllium‐10‐dated glacier record from the north‐east North Atlantic, coupled with 2‐D glacier‐climate modeling, to reconstruct Lateglacial summer air temperature patterns. Our record reveals that, contrary to the prevailing model, the last glacial advance in Scotland did not occur during the YD but predated the stadial, while the YD itself was characterized by warming‐driven deglaciation. We argue that these apparently paradoxical findings can be reconciled with regional and global climate events by invoking enhanced North Atlantic seasonality—with anomalously cold winters but warming summers—as an intrinsic response to globally increased poleward heat fluxes. Plain Language Summary: The accelerating melting of the Greenland Ice Sheet has key ramifications for North Atlantic Ocean circulation and heat transport. In the paleoclimate record, discrete periods of ocean current weakening are linked to increased meltwater input from collapsing ice sheets and are believed to have driven severe year‐round cooling of adjacent landmasses; these periods are known as stadials. Yet, research on the Younger Dryas (YD) stadial suggests that summers may have remained warm. We present a new glacier record from northwest Scotland to reconstruct patterns of stadial summer air temperature in the North Atlantic. Our data reveal that the last glacial advance did not occur during the YD, as widely assumed, but predated the stadial. The YD itself was a period of deglaciation indicative of summer climate warming. We propose that stadials are anomalous periods of high seasonality in the North Atlantic region, with cold winters but warming summers, and might be a persistent feature of AMOC disruption, both past and future. Key Points: Lateglacial fluctuations of Scottish glaciers are dated with 10 Be. Equilibrium line altitudes are resolved via glacier‐climate modeling The last pulse of glaciation culminated prior to the Younger Dryas (YD), while the stadial was characterized by deglaciation and summer warming The YD stadial was defined by anomalous thermal seasonality in the North Atlantic region, rather than by year‐round cooling